Perbankan Syariah dan Pertumbuhan Ekonomi di Indonesia : Analisis Error Correction Model - Ardana, Yudhistira (Jurnal Masharif Al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
The contribution of Islamic banks to Indonesia's economic growth has great potential to grow and develop. Islamic banks in Indonesia have shown a fairly good development, one of which is marked by an increase in service coverage in almost all provinces in Indonesia and the increasing number of Islamic banks in Indonesia. This study aims to examine the effect of Islamic banks on economic growth in Indonesia in the short and long term by using the error correction model (ECM). Sharia banking variables are proxied by the number of Islamic banks, the number of Islamic bank financing and assets of Islamic banks and economic growth is proxied by gross domestic product (GDP). The results show that in the short term the influence of Islamic banking on economic growth in Indonesia is 34.82% while the long term is 84.85%. In the long-term period the number of Islamic banks and assets of Islamic banks has a significant positive effect, while the amount of Islamic bank financing has a positive and insignificant effect. In the short-term period, the amount of Islamic bank financing and assets of Islamic banks has a negative insignificant effect, while the number of Islamic banks has a positive and insignificant effect.